EATING PATTERN AND ABO BLOOD GROUP: A RIGOROUS EXAMINATION BY SCOFF QUESTIONNAIRE IN THE FEMALE RESIDENTS OF HYDERABAD, PAKISTAN. : http://doi.org/10.46536/jpumhs/2024/14.02.511 - Syed Farhanuddin1, Jamshed Ahmed Warsi2, Rozina Mangi3, Naila noor4, Hanozia Shah5, Keenjahr Rani6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND: The significance of determining the frequency of blood typing in various diseases and eating habits grew after Landsteiner’s 1901 discovery of human genetic differences in blood typing. OBJECTIVES: The aim of the study is thus to find out any relationship between different blood groups and eating disorder. METHODOLOGY: The significance of determining the frequency of blood typing in various diseases and eating habits grew after Landsteiner’s 1901 discovery of human genetic differences in blood typing. RESULTS: The eating disorders were recognized by Scoff’s questionnaire. The statistical analysis was done on Graph Pad Prism9.the statistics and contingency options were explored to obtain P value. When normal menstruating women were compared to menopausal women, the prevalence of blood groups was 23% and 20% for A blood typing, 19.9% and 18.8% for B blood typing, 3.3% and 6.1% for AB Blood typing, and 13.8% and 14.3% for blood type O. Rh positive in typical female was 46.4% and 49.2% in menopausal ladies while Predominance of Rh negative was 3.3% and 1.1%. The study demonstrates the likelihood of an association between the aforementioned groups and the prevalence of blood typing.